Testing technosols over an ultramafic gradient for rehabilitation of diamond mine wastes in a subarctic region - Hanson, Andrea (Laurentian University of Sudbury, 2017)
Subarctic regions are recognized as one of the largest remaining pristine landscapes on earth, but are currently experiencing progressive degradation due to human activity. Mining and site rehabilitation in northern regions can be challenging largely due to the remote location of these developments. Rehabilitation is often restricted to using local mine waste materials to construct technosols. This study focused on how mines in northern regions, specifically the isolated De Beers Victor Diamond Mine, can use local mineral mine waste material to manufacture successful soil covers. Specifically, our research focused on examining the performance and success of technosols across a gradient increasing in serpentine characteristics. The objectives of the study were to, (1) determine how technosols increasing in serpentine characteristics influence vegetation establishment and microbial activity, (2) determine how the quantity of peat influences vegetation establishment and microbial activity, and (3) determine how early physical and chemical characteristics, and early plant colonization on our technosols compare to a local natural environment undergoing primary succession. We constructed a factorial experiment on two areas of mine waste at the Victor Mine, the waste rock dumpsite, and a processed kimberlite storage facility. Three test blocks were constructed on each site comprising a total of 48 5 m x 5 m experimental plots with four mineral substrate mixtures, and two levels of peat application. Mixtures consisted of various combinations of coarse and fine processed kimberlite, a silty loam marine overburden, and 20% or 40% peat, creating a gradient with ultramafic, serpentine characteristics. Each plot was fertilized at a rate of 12.5 g m-2 (NPK 8-32-16), inoculated with a microbial inoculation ‘tea’ mixture, and seeded with a variety of native vegetation. Various early physical, iv chemical and biological characteristics were examined, including early plant colonization and microbial activity. To measure microbial ...